2012
DOI: 10.1103/physrevc.85.064619
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional Langevin dynamics of heavy-ion-induced fission

Abstract: A four-dimensional dynamical model based on Langevin equations was developed and applied to calculate a wide set of experimental observables for the reactions 16 O + 208 Pb → 224 Th and 16 O + 232 Th → 248 Cf over a wide range of excitation energy. The fusion-fission and evaporation residue cross sections, fission fragment mass-energy distribution parameters, prescission neutron multiplicities, and anisotropy of angular distribution of fission fragments could be reasonably reproduced using a modified one-body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
99
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 95 publications
(179 reference statements)
2
99
0
Order By: Relevance
“…At Coulomb barrier energies, the method was successfully used to get insight into nuclear dynamics, and more specifically friction of nuclear matter [29,30,42]. The approach also demonstrated to be a pre-requisite tool for un-ambiguously understanding the dynamics and subtle time evolution of nuclei across the Businaro-Gallone transition [37].…”
Section: Discussionmentioning
confidence: 99%
“…At Coulomb barrier energies, the method was successfully used to get insight into nuclear dynamics, and more specifically friction of nuclear matter [29,30,42]. The approach also demonstrated to be a pre-requisite tool for un-ambiguously understanding the dynamics and subtle time evolution of nuclei across the Businaro-Gallone transition [37].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] it was argued that chaos-theory related ideas [14] can be used to calculate the value of the reduction coefficient k s as a function of deformation of the fissioning nucleus. The applications of this approach to calculate the coefficient k s (q) for studying different fission characteristics were rather successful, and have shown that such calculations yield almost the same results as those using the constant k s coefficient from the interval 0.25 < k s < 0.5 [6,12,15].…”
mentioning
confidence: 93%
“…The detailed description of the model could be found in Refs. [2,4] and here we give only a short summary. Three collective shape coordinates and the orientation degree of freedom (K coordinate) were considered dynamically from the ground state deformation to the scission into fission fragments.…”
mentioning
confidence: 99%
See 2 more Smart Citations